Clinical Implications of ECG in Patients Presenting to ED with Drug-overdose and Organo-phosphorous Poisoning - Jagadesha Selvan; Darpanarayan Hazra; Gina M. Chandy; Priya Ganesan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Drug overdose and organo-phosphorous (OP) poisoning are one of the most common forms of deliberate self-harm (DSH) in our society. Some drugs and OP compounds have well-described electrocardiographic (ECG) manifestations in the event of toxicity. This study aims to determine the clinical implications of an electrocardiogram (ECG) in patients with an alleged history of DSH (drug overdose and/or OP poisoning) presenting to the ED. Methodology: We conducted this retrospective study over one and a half years (October 2018 to April 2020). Demographical data, clinical presentations, and ECG findings were extracted from the hospital’s electronic database, coded, and analyzed. Results: Our study population included 364 (0.32%) patients with DSH (OP poisoning and drug overdose), of which the majority (n-224; 61.5%) had presented with a drug overdose. The mean age of the cohort was 33.9 (SD: 13.1) years, with a female preponderance (n-222; 60.9%). The most common presenting complaints were vomiting (n-180; 49.5%), other gastrointestinal complaints (n-146; 40.1%), and giddiness (n-122; 33.5%). At the presentation to ED, the majority had a qSOFA ≥2 (n-212; 58.3%). The most common drugs noted to be consumed singly included benzodiazepines (n-42, 11.5%), paracetamol (n-38; 10.4%), and tricyclic antidepressant (n-20; 5.5%). Polydrug intoxication was seen in 68 (18.7%), and co-ingestion with OP was seen in 26 (7.2%) patients. ECG changes (QTc prolongation) were noted in 187 (51.4%: p-value 0.003) patients. All patients were advised to be admitted after initial stabilization and emergency management; however, 73 (20.1%) patients left the ED against medical advice. During their hospital stay, seven (1.9%) patients succumbed to their illness. Conclusion: Middle-aged female patients are more prone to DSH, with gastrointestinal complaints as the most common presenting symptom. In patients with drug overdose or OP poisoning, ECG changes (QTc prolongation) were noted in the majority of the study population.